The Relationship between Diet and Physical Activity with the Nutritional Status of More Adolescents at SMP Negeri 1 Campurdarat Tulungagung - Pusparini, Nayunda Putri; Fajar, Ibnu; Hadisuyitno, Juin; Komalyna D, I Nengah Tanu (Politeknik Kesehatan Kemenkes Malang, 2024)
Background: Overnutrition or obesity is a condition where body weight increases due to the accumulation of body fat. One of the causes of nutritional status is a change in excessive eating patterns and lack of physical activity. Food consumption levels refer to the amount of food and drink consumed by individuals, families or communities in a certain time period. Apart from the level of food consumption, the factor that influences nutritional status is physical activity. The definition of physical activity is any body movement that is caused by the work of skeletal muscles and increases energy and energy expenditur. Objective: to determine the relationship between the level of food consumption and physical activity with the incidence of adolescent nutritional status at SMP Negeri 1 Campurdarat. Methods: This research includes quantitative research, a type of analytic survey research with a case control research design, Result: The results of the chi square analysis of the relationship between the level of food consumption and the nutritional status of the respondents had a significance value of 0.009 or <0.05 and the relationship between the level of food consumption and the nutritional status of the respondents had a significance value of 0.003 or <0.05 so that it can be said that there is a relationship. Conclusion: Shows that there is a relationship between excessive eating patterns with more nutritional status in adolescents and less physical activity with the incidence of overweight adolescents.